Genomic Differences Between the Sexes in a Fish Species Seen Through Satellite DNAs - Crepaldi, Carolina; Martí, Emiliano; Gonçalves, Évelin Mariani; Martí, Dardo Andrea; Parise-Maltempi, Patricia Pasquali (Frontiers in Genetics, 2021)
Neotropical fishes have highly diversified karyotypic and genomic characteristics and present many diverse sex chromosome systems, with various degrees of sex chromosome differentiation. Knowledge on their sex-specific composition and evolution, however, is still limited. Satellite DNAs (satDNAs) are tandemly repeated sequences with pervasive genomic distribution and distinctive evolutionary pathways, and investigating satDNA content might shed light into how genome architecture is organized in fishes and in their sex chromosomes. The present study investigated the satellitome of Megaleporinus elongatus, a freshwater fish with a proposed Z1Z1Z2Z2/Z1W1Z2W2 multiple sex chromosome system that encompasses a highly heterochromatic and differentiated W1 chromosome. The species satellitome comprises of 140 different satDNA families, including previously isolated sequences and new families found in this study. This diversity is remarkable considering the relatively low proportion that satDNAs generally account for the M. elongatus genome (around only 5%). Differences between the sexes in regards of satDNA content were also evidenced, as these sequences are 14% more abundant in the female genome. The occurrence of sex-biased signatures of satDNA evolution in the species is tightly linked to satellite enrichment associated with W1 in females. Although both sexes share practically all satDNAs, the overall massive amplification of only a few of them accompanied the W1 differentiation. We also investigated the expansion and diversification of the two most abundant satDNAs of M. elongatus, MelSat01-36 and MelSat02-26, both highly amplified sequences in W1 and, in MelSat02-26’s case, also harbored by Z2 and W2 chromosomes. We compared their occurrences in M. elongatus and the sister species M. macrocephalus (with a standard ZW sex chromosome system) and concluded that both satDNAs have led to the formation of highly amplified arrays in both species; however, they formed species-specific organization on female-restricted sex chromosomes. Our results show how satDNA composition is highly diversified in M. elongatus, in which their accumulation is significantly contributing to W1 differentiation and not satDNA diversity per se. Also, the evolutionary behavior of these repeats may be associated with genome plasticity and satDNA variability between the sexes and between closely related species, influencing how seemingly homeologous heteromorphic sex chromosomes undergo independent satDNA evolution.